The Differences of T-Regulator Cells, Alanine Aminotransferase Serum and Aspartate Aminotranspherase Between Hepatitis B Chronic Patients with and without Liver Fibrosis - Yostila Derosa; Nasrul Zubir; Raveinal Arnelis (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: Hepatitis B is acute or chronic liver inflammation caused by hepatitis B viral and can progress to hepatic chirrosis or liver cancer. Chronic hepatitis B has a high risk for liver fibrosis. Chronic inflammation and liver fibrosis are interrelated processes. This study aimed to determine the differences in T-regulator cells, Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) between chronic hepatitis B patients with and without liver fibrosis.Method: This study used a cross-sectional method for patients diagnosed with chronic hepatitis B in the Inpatient and Outpatient Department of the Internal Medicine Department  DR. M. Djamil Padang and other hospitals in Padang city for 6 months. Samples were selected by consecutive sampling according to inclusion and exclusion criteria. Liver fibrosis is identified by fibroscan. Data were analyzed by SPSS 21.0.Results: thirty-two patients were diagnosed with chronic hepatitis B and 50% had liver fibrosis. The levels of T-regulator cells in chronic hepatitis B patients without liver fibrosis were 2.08% and liver fibrosis 2.25%, but this difference was not statistically significant (p 0.05). Mean ALT levels in the group without fibrosis were 19 IU/L (7IU/L-71IU/L) and liver fibrosis 61 IU / L (13IU/L-625IU/L). The mean AST level in the group without fibrosis were 15.5 IU/L (10IU/L-32IU/L) and liver fibrosis 35.5 IU/L (10IU/L-476IU/L). The difference between ALT and AST in the two groups was significant (p 0.05). Hepatitis B patients with liver fibrosis had higher ALT and AST levels than without fibrosis.Conclusion: There were differences levels of T-regulator cells in the two groups, but it was not statistically significant. ALT and AST levels were higher in the liver fibrosis group and statistically significant.